Optimization of ready-to-drink Chrysanthemum flower tea formulation based on bioactive compounds and sensory properties - Julianti Elisa; Masniary Lubis Linda; Gunawan Michael (BIO Web of Conferences)
This study aims to optimize the formulation of ready-to-drink Chrysanthemum flower tea using Response Surface Methodology-Box Behnken Design (RSM-BBD) to meet modern consumer preferences for health-oriented and convenient beverages. The optimal formulation was determined based on maximizing bioactive compounds, including total phenolics, flavonoids, and anthocyanins, as well as antioxidant activity and sensory acceptability. The best formulation involved brewing 2 g of Chrysanthemum flower powder in water at 90°C with 14.281% sugar. This formulation yielded a total phenolic content of 535.752 mg GAE/g, total flavonoid content of 49.909 mg QE/g, and anthocyanin content of 5.929 mg/L, indicating significant health-promoting properties. Sensory evaluations highlighted the formulation's excellent taste, aroma, and color, making it highly appealing to consumers. The findings have practical implications for the beverage industry, providing a scientific basis for developing functional and consumer-friendly herbal drinks. This optimized Chrysanthemum tea formulation aligns with the growing demand for health- conscious products that combine nutritional benefits with sensory satisfaction.